Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Profil Pelajar Pancasila dalam Mata Pelajaran Ekonomi di SMA N 1 Singaraja - Ni Luh Putu Ayu Desy Pratiwi; Luh Indrayani (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
This development research was carried out to develop Student Worksheets (LKPD) based on Profil Pelajar Pancasila in accordance with students needs in economics learning. The aimed of this study was to determine the design, validity, and feasibility of LKPD based on Profil Pelajar Pancasila in Economics at SMAN 1 Singaraja. Learning material experts, learning media experts, and class XII students as test subjects. 4D Models (define, design, develop, disseminate) as the development model used. Data were collected using questionnaires (validation sheets and student responses), observations and unstructured interviews. Data were analyzed using quantitative and qualitative descriptive analysis.Â The results obtained are products in the form of LKPD, including the results of: (a) design description with stages of define, design, develop, disseminate; (b) LKPD based on the Profil Pelajar Pancasila is declared feasible in accordance with the validity test results from material experts with a value of 95% and from media experts with a value of 97%; (c) LKPD based on the Pancasila Student Profile was declared feasible with a score of 89% from trials with small groups. Thus, LKPD based on the Profil Pelajar Pancasila is suitable for use in the learning process.